Analisis Aplikasi Yang Berjalan dan Rencana Proyek Dengan Metode New Information Economics Pada Asuransi Syariah AJB Bumi Putera 1912 - Bambang Zulkarnain (Jurnal Teknologi Informasi dan Komputer, 2015)
AJB  Bumiputera  1912  is  one  of  the  Islamic  insurance  company,  where  the  products themselves  oriented  life  insurance.  AJB  Bumiputera  1912  has  several  application  systems, infrastructure, services, and ongoing management (lights-on) as well as the projects being developed. Management Party wants to know the benefits and impacts of lights-on as well as projects inthe company and also the value of her tuning of the strategic direction. The author proposes to analyze lights on the project along with New Information Economics method using four practices, namely Strategic Demand / Supply Planning, Alignment, Innovation, and Prioritization. The results obtained by the SWOT matrix the company has four referral strategies, namely Enhance  customer  relationships,  Expanding  market  share,  increase  work  efficiency  and  Improve relations  with  business  partners.  While  the  lights-on  who  were  in  stable  condition  is  a  platform (hardware & software), Maintenance, Training, Budgeting and planning. Lights-on is in a state of enhanced only when needed is the application of sharia E-plus, office desktop, Helpdesk and Network. Lights-on who are in a satisfactory condition include BIL application of Sharia, Web GL, and the Portal  Server.  The  project  is  a  project  that  should  take  precedence  over  the  VPN-IP  then Datawarehouse, DRC and the SMS Service.Keywords : Application Analysis, Project Plan, New Information Economics Methods.